Linking AM-PAC Mobility and Daily Activity to the PROMIS Physical Function Metric. Issue 8 (4th March 2021) - Thackeray, Anne; Hanmer, Janel; Yu, Lan; McCracken, Polly; Marcus, Robin
Abstract: Objective: The purpose of this study was to link Activity Measure for Post-Acute Care (AM-PAC) Mobility and Daily Activity scales to the PROMIS Physical Function (PF) allowing for a common metric across scales. Methods: Cross-sectional study of patients 18 years and older presenting to 1 of 8 outpatient rehabilitation clinics in southwestern Pennsylvania. Patients completed one survey with questions from the AM-PAC Daily Activity and Mobility short forms, and the PROMIS PF item bank. Using item response theory, 2 rounds of fixed-parameter calibration were performed. In the first, the AM-PAC Daily Activity and Mobility items were calibrated with 27 fixed item parameters from the PROMIS PF. Second, the AM-PAC Daily Activity items were calibrated with 11 PROMIS Upper Extremity fixed item parameters. This process uses the construct of physical function and equates AM-PAC items on the same underlying measurement scale for the PROMIS PF. Results: Both scales measured a wide range of functioning and demonstrated good calibration. Data were appropriate for a fixed-parameter item response theory-based crosswalk. AM-PAC Daily Activity and Mobility raw scores were mapped onto the PROMIS PF metric. AM-PAC Daily Activity scores were also mapped onto the PROMIS PF Upper Extremity metric. Conclusion: Question items from the AM-PAC Daily Activity, AM-PAC Mobility, and PROMIS PF similarly measure the construct of physical function. This consistency allows for a crosswalk of AM-PAC scores onto the PROMIS PF metric. Impact: Crosswalk tables developed in this study allow for converting scores from the AM-PAC Daily Activity and Mobility scales to the PROMIS PF metric. This will facilitate monitoring of longitudinal change in function over time and across settings.